Comparative stigmatic transcriptomics reveals self and cross pollination responses to heteromorphic incompatibility in Plumbago auriculata Lam. - Hu, Di; Lin, Di; Yi, Shouli; Gao, Suping; Lei, Ting; Li, Wenji; Xu, Tingdan (Frontiers in Genetics, 2024)
“Heteromorphic self-incompatibility” (HetSI) in plants is a mechanism of defense to avoid self-pollination and promote outcrossing. However, the molecular mechanism underlying HetSI remains largely unknown. In this study, RNA-seq was conducted to explore the molecular mechanisms underlying self-compatible (SC, “T × P” and “P × T”) and self-incompatible (SI, “T × T” and “P × P”) pollination in the two types of flowers of Plumbago auriculata Lam. which is a representative HetSI plant. By comparing “T × P” vs. “T × T”, 3773 (1407 upregulated and 2366 downregulated) differentially expressed genes (DEGs) were identified, 1261 DEGs between “P × T” and “P × P” (502 upregulated and 759 downregulated). The processes in which these DEGs were significantly enriched were “MAPK (Mitogen-Activated Protein Kinases-plant) signaling pathway”, “plant-pathogen interaction”,“plant hormone signal transduction”, and “pentose and glucuronate interconversion” pathways. Surprisingly, we discovered that under various pollination conditions, multiple notable genes that may be involved in HetSI exhibited distinct regulation. We can infer that the HetSI strategy might be unique in P. auriculata. It was similar to “sporophytic self-incompatibility” (SSI) but the HetSI mechanisms in pin and thrum flowers are diverse. In this study, new hypotheses and inferences were proposed, which can provide a reference for crop production and breeding.